Areté e Paideia : a formação do homem político no diálogo primeiro Alcibíades de Platão - Gomes, Erick Vinicius Santos (2018)
The research in progress has as its structural focus the political man formation study from Platonic perspective of areté (moral excellence) and Greek paideia (education). First Alcibiades dialogue was chosen as the research object because we believe that speaking of political areté in Plato’s First Alcibiades consists exactly in reflecting on Athenian political education philosophical foundations, as well as several knowledge forms, which somehow constitute the existence of the polis, of its social structures, and of political man formation. By fair means of foul, to consider a philosophy of education from Platonic ontology means to seek the principles of a paideia project which support is the disposition of psyché (soul) elements and episteme (science) to teach the art of governing and to be governed by perfecting the soul and the search for knowledge of oneself, because, for Plato, if every citizen is educated to do what is up to him, that is, to do what he possesses knowledge about, putting all his excellences into function of the polis’ greater good and happiness, as a result, there will be harmony between them (political men) and in the city-state. Thus, justice itself will reign. For Plato, this is a principle which must guide the action of men who seek city-state government. According to this perspective, the research moves towards the notion that self-knowledge (gnōthi seauton), techné (art) and episteme (science) are the components of paideia’s soul project that is found in Alcibiades I – which somehow corresponds to the philosophical treatment that Socrates aspires to the city-state and to Alcibiades. In order to realize this project, Socrates will indicate to the incomplete 20 years old ephebe and to Athens the Delphos oracle recommendation - gnōthi seauton (know yourself): before the attempt of love demonstration (Eros) by the city soul and by Alcibiades, Socrates, in a dialectical way (dialectic arises represented by the use of elenchus as a pedagogical resource), strives to indicate alétheia (truth) path to Alcibiades - in this regard, Socrates, as an educator, wishes to point out to Alcibiades the fluxes path (change), the path of what “is” - of what is the soul. Trying to educate the city-state’s soul and Alcibiades’ for virtue, Socrates understands that one cannot teach what is in permanent flux. The wise and educator is the one who recognizes true and false images. The true master, along with the pupil, as far as possible, will always be looking toward the beautiful and unchanging. Through the soul, the master leads the pupil to perceive the relationship between things that “are” and immutable things - Alcibiades will have access to immutable forms if he learns to use the third eye, the eye of the soul (phsyché), since it is in the soul’s gaze that all the fullness of Socratic footprint resides.